Effects of PCSK9 inhibitor on adverse limb outcomes in patients with critical limb ischemia. (25th November 2020) - Sato, Y; Uzui, H; Aiki, Y; Aoyama, D; Yamaguchi, J; Nodera, M; Shiomi, Y; Hasegawa, K; Ikeda, H; Tama, N; Fukuoka, Y; Morishita, T; et al.
Abstract: Background: The proprotein convertase subtilisin/kexin type 9 inhibitor (PCSK9-I), evolocumab, reduced the risk of cardiovascular event in patients with peripheral artery disease in FOURIER trial. However, the effects of evolocumab on favorable limb outcomes in patients with critical limb ischemia (CLI) is still unclear. Purpose: The aim of this study was to evaluate the impacts of evolocumab on favorable limb outcomes and lipid profile in patients with CLI. Methods: This was a single center, prospective observational study. A total of 39 patients with CLI were enrolled between November 2016 to May 2019. The subjects were divided into 2 groups based on evolocumab administration: evolocumab-treated group: E group (mean 69.4±11.7 years, n=14) and evolocumab non-treated group: Non-E group (mean 74.0±8.8 years, n=25). Baseline characteristics were assessed at admission. Lipid profile was evaluated at admission, 1, 3, 6, 12 and 18 months. The primary outcome was defined 18-month amputation-free survival (AFS). The secondary outcomes were defined 18-month overall survival (OS) and wound-free limb salvage. Mean follow-up period was 18±11 months. Results: The patients in E group had greater reduction in levels of LDL cholesterol and non-HDL cholesterol than those in Non-E group over time. The reduction in MDA-LDL level was maintained at 1, 3, 6, 12 months, respectively. The 18-month AFS rate in the E-group was significantly higher than those in the Non-E group (log-rank p=0.02). The patients receiving evolocumab had a lower hazard regarding AFS (hazard ratio, 0.12; 95% confidence interval, 0.02–0.94; P=0.043) and a higher proportion of wound-free limb salvage at 12 months (E group [92%] vs Non-E group [57%], P=0.034) and 18 months (92% vs 52%, P=0.03). Otherwise, evolocumab administration was not associated with 18-month OS (log-rank p=0.053). Conclusions: Evolocumab administration may be associated with the favorable outcome of 18-month AFS in the patients with CLI. Additionally, long-term administration of evolocumab over 12 months may improve wound-free limb salvage. Funding Acknowledgement: Type of funding source: None